Perbedaan Ajaran dan Praktik Dalam Organisasi Muhammadiyah dan Nahdlatul Ulama di Purwokerto - Mulyani, Mulyani (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
This paper aims to describe the differences in teachings and practices in the Muhammadiyah and Nahdatul ulama organisations in Purwokerto, explaining the history of the entry of Muhammadiyah and Nahdlatul ulama (NU) organisations in Purwokerto. The method used in studying the topic raised is a qualitative descriptive method based on direct observation and interviews with one of the students from Muhammadiyah and Nahdlatul Ulama. in this article at the first point explains the entry of the Muhammadiyah Islamic organisation and the Nahdlatul Ulama Islamic organisation in Purwokerto which was established in 1922 for Muhammadiyah and 1932 for Nahdlatul ulama. In the next point explains about the differences in worship practices between Muhammadiyah and Nahdlatul Ulama organisations in Purwokerto include differences in morning prayers and terawih prayers that use qunut prayers, differences regarding tahlilan, grave pilgrimage and others, but with that difference the people in Purwokerto are increasingly tolerant.